1992
DOI: 10.1063/1.461987
|View full text |Cite
|
Sign up to set email alerts
|

Molecular open shell configuration interaction calculations using the Dirac–Coulomb Hamiltonian: The f 6-manifold of an embedded EuO9−6 cluster

Abstract: Prediction of the adsorption behavior of elements 112 and 114 on inert surfaces from ab initio Dirac-Coulomb atomic calculations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(61 citation statements)
references
References 24 publications
2
59
0
Order By: Relevance
“…Vertical excitation energies for the neutral I 2 molecule were examined using the general open shell CI (COSCI) routine 30 in the modified DIRAC program. COSCI does full CI calculation for the orbital (spinor) space specified.…”
Section: Test Calculationsmentioning
confidence: 99%
“…Vertical excitation energies for the neutral I 2 molecule were examined using the general open shell CI (COSCI) routine 30 in the modified DIRAC program. COSCI does full CI calculation for the orbital (spinor) space specified.…”
Section: Test Calculationsmentioning
confidence: 99%
“…Doing so, allows for con-2 vergence with a desired accuracy. As starting point for developing our crystal orbital program 24 we used the MOLFDIR program of Nieuwpoort et al 4 This program, which accepts as input the universal, the geometrical, and other basis sets, did not accept our fitted basis functions numerical results. The reason for this was that the overlap matrix of our basis functions was not Merit function = 2.2716E y 4 Merit function is = 6.4009E y 5…”
Section: Fitting Relativistic Atomic Orbitals With Gaussians and Genementioning
confidence: 99%
“…respectively. The adsorbed spectra showed that when the wavelength ranged from 350-550 nm, the sharp peaks originated from the transitions with the f-configuration from 7 F 0 to the excitation states (Visser et al 1992 ceramic. However, the intensities of the peaks in the excitation spectra increased in order of 0.2, 0.4, 0.6, 0.8, 1.0, 1.5 and 2 mol%.…”
Section: +mentioning
confidence: 99%